Exploration of Chalcones as Antimicrobial agents: Synthesis, Characterization, Antimicrobial Evaluation and Molecular Docking studies: Synthesis , charactrization , antimicirobial and docking evaluation of some new chalcones - Addipalli, Kanaka Raju; Yejella, Rajendra Prasad; Vedula, Girija Sastry (Iranian Journal of Pharmaceutical Sciences, 2025)
Although many medications are available to treat infectious infections, their therapeutic efficacy is hampered by systemic toxicities, drug resistance, hypersensitivity, and a narrow antibacterial spectrum. Based on the above facts, we synthesized and evaluated some new chalcones’ antibacterial and antifungal properties. A group of natural compounds called chalcones has a broad spectrum of biological activity. The Claisen-Schmidt condensation of 4-tert-butyl-2,6-dimethyl-3,5-dinitro acetophenone with a variety of substituted aromatic and heteroaromatic aldehydes yielded some new chalcones with different substituents in consideration of the wide range of biological activities related to chalcones. Column chromatography and recrystallization techniques were used to purify the produced chalcones. IR, 1H NMR, and elemental analysis data characterized the purified chalcones. These substances underwent additional testing for antimicrobial activity using the serial tube dilution technique. Antibacterial testing revealed potent activity for chalcones R1, R5, R6, and R18 (MIC: 32 µg/mL), attributed to electron-withdrawing groups like dichloro, nitro, and difluoro substituents. Antifungal studies identified R1, R3, and R18 as the most effective (MIC: 16 µg/mL against Aspergillus niger and Candida tropicalis), with SAR analysis emphasizing the roles of halogens and methoxy groups in enhancing activity. Quality evaluation of the protein PDB: 4AMV confirmed its suitability for molecular docking studies using the SAVES server and binding pocket analysis using CASTp and BIOVIA Discovery studio. Docking of chalcones against PDB: 4AMV using Auto Dock Vina module of PyRx 0.8 revealed binding affinities ranging from −7.2 to −8.4 kcal/mol, with ciprofloxacin (standard) showing −8.3 kcal/mol. Chalcone R6 exhibited the greatest affinity for binding (-8.4 kcal/mol) and robust interactions, including hydrogen bonds and hydrophobic contacts. R1, R5, and R9 also demonstrated significant affinities (−8.2 to −8.0 kcal/mol). These findings highlight chalcones, particularly R6, as promising candidates for further antimicrobial development.